2003
DOI: 10.1016/s0166-4972(01)00107-9
|View full text |Cite
|
Sign up to set email alerts
|

Is more always better? An exploration of the differential effects of functional integration on performance in new product development

Abstract: The objective of this paper is to explore the relationship between performance in new product development (hereinafter NPD) and functional integration under different conditions of project uncertainty. Functional integration is conceived as a two-dimensional concept, encompassing a behavioural -collaboration -and a structural -interaction -dimension.This study is based on 92 questionnaires looking at NPD activities in more than 40 British and Dutch companies from various industrial sectors. The results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 36 publications
2
36
0
19
Order By: Relevance
“…Parthasarthy and Hammond 2002, Gomes et al 2003, Hirunyawipada et al 2010, Baron and Tang 2011. These relationships, which are not covered in the current paper, highlight the relevance of creativity and the sub-phases of conversion ability under consideration in order for innovation efforts to be successful.…”
Section: Discussionmentioning
confidence: 86%
“…Parthasarthy and Hammond 2002, Gomes et al 2003, Hirunyawipada et al 2010, Baron and Tang 2011. These relationships, which are not covered in the current paper, highlight the relevance of creativity and the sub-phases of conversion ability under consideration in order for innovation efforts to be successful.…”
Section: Discussionmentioning
confidence: 86%
“…II also enables sharing of knowledge across functions and manufacturing plants (Roth, 1996;Narasimhan & Kim, 2002;Caridi et al, 2012), which helps to facilitate product innovation by acquiring internal product development knowledge across business functions, such as marketing, R&D and production. Gomes et al (2003) found a significant relationship between performance in product innovation and internal integration, through a survey of 40 British and Dutch companies from various sectors. Supporting this finding, Kahn and Mentzer (1996) indicate that the level of cross-functional integration is significantly related to new product development performance.…”
Section: Internal Integration and Product Innovationmentioning
confidence: 98%
“…), (2) influences of some relevant factors on CFI effectiveness (e.g., Leenders & Wierenga, 2002;Song, Montoya-Weiss, & Schmidt, 1997, etc. ), and (3) impacts of functional types and development phases on CFI effectiveness (e.g., Gomes, Weerd-Nederhof, Pearson & Cunha, 2003;Song et al, 1998).…”
Section: Introductionmentioning
confidence: 99%